2011
DOI: 10.1098/rstb.2011.0028
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of gene function in behaviour

Abstract: Behaviour genetic research has shown that a given gene or gene pathway can influence categorically similar behaviours in different species. Questions about the conservation of gene function in behaviour are increasingly tractable. This is owing to the surge of DNA and 'omics data, bioinformatic tools, as well as advances in technologies for behavioural phenotyping. Here, we discuss how gene function, as a hierarchical biological phenomenon, can be used to examine behavioural homology across species. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 98 publications
2
46
0
Order By: Relevance
“…In D. montana, we found two gene clusters which showed significant enrichment for muscle protein (Table 1, orange), while in D. virilis there were several clusters significantly enriched for protein signalling (Table 1, pink). Although the above mentioned functional clusters were only significantly enriched in one species, these processes are likely to be a component of cold acclimation in both of the species as we also found genes (Fitzpatrick et al, 2005;Reaume and Sokolowski, 2011;Martin and Orgogozo, 2013). Candidate gene studies however generally focus upon a subset of genes which have a large influence on a particular trait.…”
Section: Go Term Enrichment Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…In D. montana, we found two gene clusters which showed significant enrichment for muscle protein (Table 1, orange), while in D. virilis there were several clusters significantly enriched for protein signalling (Table 1, pink). Although the above mentioned functional clusters were only significantly enriched in one species, these processes are likely to be a component of cold acclimation in both of the species as we also found genes (Fitzpatrick et al, 2005;Reaume and Sokolowski, 2011;Martin and Orgogozo, 2013). Candidate gene studies however generally focus upon a subset of genes which have a large influence on a particular trait.…”
Section: Go Term Enrichment Analysismentioning
confidence: 93%
“…Candidate gene approaches, whereby genes of interest identified in a model species are functionally examined in others, have often been successful and have indicated that gene function tends be conserved across species (Fitzpatrick et al, 2005;Reaume and Sokolowski, 2011;Martin and Orgogozo, 2013). In contrast, quantitative genetics studies have often suggested that traits important to adaptation are polygenic, and quantitative trait loci (QTL) may have low repeatability between species (Arbuthnott, 2009;Huang et al, 2012;Rockman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These findings have occasionally caused misunderstandings as to the correct interpretation of homologous characters [68][69][70] and new ways to define them are being continuously discussed [66,[71][72][73]. The same kind of difficulties are expected when discussing homology in behavioural traits and, especially, their underlying genetic and developmental bases [63].…”
Section: Different Traits One Phenotypementioning
confidence: 99%
“…Not only are common behaviours like aggression, sex, or learning and memory present across taxa [63], but also more specific ones, such as tool use [64] or web-spinning [65]. A key developmental question is: can similar behaviours in different taxa rest upon completely different neuronal and/or genetic mechanisms or do similar behaviours (independently of the taxon) rely (or even have to rely) on conserved neuronal and/or genetic mechanisms (figure 1)?…”
Section: Different Traits One Phenotypementioning
confidence: 99%
See 1 more Smart Citation